The Photocatalytic Activity and Compact Layer Characteristics of TiO2 Films Prepared Using Radio Frequency Magnetron Sputtering - H. C. Chang; H. H. Huang; C. Y. Wu; R. Q. Hsu; C. Y. Hsu (International Journal of Photoenergy)
TiO2 compact layers are used in dye-sensitized solar cells (DSSCs) to prevent charge recombination between the electrolyte and the transparent conductive substrate (indium tin oxide, ITO; fluorine-doped tin oxide, FTO). Thin TiO2 compact layers are deposited onto ITO/glass by means of radio frequency (rf) magnetron sputtering, using deposition parameters that ensure greater photocatalytic activity and increased DSSC conversion efficiency. The photoinduced decomposition of methylene blue (MB) and the photoinduced hydrophilicity of the TiO2 thin films are also investigated. The photocatalytic performance characteristics for the deposition of TiO2 films are improved by using the Grey-Taguchi method. The average transmittance in the visible region exceeds 85% for all samples. The XRD patterns of the TiO2 films, for sol-gel with spin coating of porous TiO2/TiO2 compact/ITO/glass, show a good crystalline structure. In contrast, without the TiO2 compact layer (only porous TiO2), the peak intensity of the anatase (101) plane in the XRD patterns for the TiO2 film has a lower value, which demonstrates inferior crystalline quality. With a TiO2 compact layer to prevent charge recombination, a higher short-circuit current density is obtained. The DSSC with the FTO/glass and Pt counter electrode demonstrates the energy conversion efficiency increased.